PRAGMATIC FEATURES OF PROFESSIONAL ANECDOTES (Scientific journal of the Fergana State University, 2023)
The article analyzes the division of anecdotes into classifications and the professional anecdotes included in this classification. Attention is also paid to the lingvoculturological properties of anecdotes.